(untitled) (Modern American Journal of Medical and Health Sciences, 2026)
The implementation of the results of the first study based on epidemiological monitoring, pharmacoepidemiological analysis and the developed preventive program led to the following: 1) a “regional portrait” of the population with COVID-19-associated lung injury was formed, which made it possible to use it for active preventive measures. It was widely used in practical activities; 2) early diagnosis of premorbid and comorbid background of COVID-19 lung injury was significantly improved; 3) the risk of thromboembolic complications associated with COVID-19 lung injury was reduced by more than 30% (every third patient); 4) the number of prescribed drugs with potential risks was reduced by 30%; 5) adverse effects and manifestations of drugs were prevented by up to 10% in COVID-19 lung injury; 6) client mortality rate decreased by 20%, rate of appropriate and safe prescribing of antibiotic therapy improved by 90%.